2017
DOI: 10.1111/sapm.12171
|View full text |Cite
|
Sign up to set email alerts
|

Real Solutions of the First Painlevé Equation with Large Initial Data

Abstract: We consider three special cases of the initial value problem of the first Painlevé (PI) equation. Our approach is based on the method of uniform asymptotics introduced by Bassom et al. A rigorous proof of a property of the PI solutions on the negative real axis, recently revealed by Bender and Komijani, is given by approximating the Stokes multipliers. Moreover, we build more precise relation between the large initial data of the PI solutions and their three different types of behavior as the independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 21 publications
5
29
0
Order By: Relevance
“…Actually, the asymptotic behavior of the Stokes multipliers in Theorem 2.2 is valid not only for fixed C, but also uniformly for all C(ξ) in the corresponding regions, and thus we may assume C(ξ) depends on ξ. Let C(ξ) = 1 2 pξ −4/5 with p fixed, the following corollary is also a direct consequence of Theorem 2.2, which gives an asymptotic classification of P I solutions for fixed p and large negative H. It can be regarded as another kind of nonlinear eigenvalue phenomenon similar to the initial value problem in [2,3,24]. Corollary 2.5.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Actually, the asymptotic behavior of the Stokes multipliers in Theorem 2.2 is valid not only for fixed C, but also uniformly for all C(ξ) in the corresponding regions, and thus we may assume C(ξ) depends on ξ. Let C(ξ) = 1 2 pξ −4/5 with p fixed, the following corollary is also a direct consequence of Theorem 2.2, which gives an asymptotic classification of P I solutions for fixed p and large negative H. It can be regarded as another kind of nonlinear eigenvalue phenomenon similar to the initial value problem in [2,3,24]. Corollary 2.5.…”
Section: Resultsmentioning
confidence: 91%
“…In particular, Bender and Komijani [2] observed that the three types P I solutions appear alternatively as one initial data fixed and the other varying continuously. Recently, Long et al [24] gave rigorous proof to this phenomenon, obtained an asymptotic classification of the P I solutions with respect to the initial data, and built some limiting-form connection formulas.…”
Section: Connection Problems Of P Imentioning
confidence: 99%
See 3 more Smart Citations